DESAIN KREATIF DALAM IBADAH PEMUDA: UPAYA MENINGKATKAN PARTISIPASI JEMAAT - Sri Musara Siahaan; Feronica Damayanty Tinambunan; Damayanti Nababan (CV. Denasya Smart Publisher, 2024)
This research aims to determine creativity in generating congregational crafts in worshiping at church. This research uses qualitative research methods with data collection. The population of this study was all church members. where the researcher is the key instrument. The results of this research indicate that the congregation is less interested in crafts in coming to church to worship. This can be seen from the number of congregations attending the church. Based on the results of this research, creativity can be the main driving force in encouraging congregational craftsmanship in worshiping at church. By exploring creative concepts and practices, we explore how these efforts can enrich the congregation's worship experience and strengthen the spiritual bond with the church as a place of worship.